Colely
Colely
02-06-2017
Mathematics
contestada
If f (x)=-3x+3, then f^-1(x)=
Respuesta :
apologiabiology
apologiabiology
02-06-2017
1. replace f(x) with y
2. solve for x
3.replace x wieth f^-1(x) and y with x
f(x)=-3x+3
y=-3x+3
y-3=-3x
divide both sides by -3
(3-y)/3=x
f^-1(x)=(3-x)/3
Answer Link
VER TODAS LAS RESPUESTAS ( 75+ )
Otras preguntas
what is 25% of 500.00
what is 25% of 500.00
what is 25% of 500.00
what is 25% of 500.00
what is 25% of 500.00
what is 25% of 500.00
what is 25% of 500.00
what is 25% of 500.00
what is 25% of 500.00
what is 25% of 500.00